2017
DOI: 10.1080/15384047.2017.1294288
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic treatment promotes triple-negative breast cancer invasion via vasculogenic mimicry

Abstract: Agents that target angiogenesis have shown limited efficacy for human triple-negative breast cancer (TNBC) in clinical trials. Along with endothelium-dependent vessels, there is also vasculogenic mimicry (VM) in the microcirculation of malignant tumors. The role of VM is not completely understood regarding anti-angiogenic treatment. In this study, human TNBC MDA-MB-231 and Hs578T and non-TNBC MCF-7 and BT474 tumor-bearing mice were treated with sunitinib, an anti-angiogenic drug, using a clinically relevant sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 43 publications
(51 reference statements)
1
72
0
1
Order By: Relevance
“…Overexpression of factors regulating VM in breast tumors, such as HIF1alpha, VE-cadherin, and EPHA2 has also been reported (33)(34)(35)(36). In a mouse breast cancer model, inhibition of angiogenesis promoted VM by expression of VE-Cadherin and other VM regulators in triple-negative tumors (37). In the MDA-MB-231 cell line (derived from a triple-negative tumor) which can form a pattern of tubular structures in matrigel, low expression of miR-204 was observed, while overexpression of miR-204 decreased the VM.…”
Section: Factors Involved In Vm In Breast Cancermentioning
confidence: 89%
“…Overexpression of factors regulating VM in breast tumors, such as HIF1alpha, VE-cadherin, and EPHA2 has also been reported (33)(34)(35)(36). In a mouse breast cancer model, inhibition of angiogenesis promoted VM by expression of VE-Cadherin and other VM regulators in triple-negative tumors (37). In the MDA-MB-231 cell line (derived from a triple-negative tumor) which can form a pattern of tubular structures in matrigel, low expression of miR-204 was observed, while overexpression of miR-204 decreased the VM.…”
Section: Factors Involved In Vm In Breast Cancermentioning
confidence: 89%
“…Bevacizumab (trade name Avastin) slightly contributed to progression-free survival (PFS) but not overall survival (OS) in glioma patients 3 . Several preclinical studies speculate that vasculogenic mimicry (VM) contributes to anti-angiogenesis therapeutic resistance [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, VEGFA plays a key role in the process of angiogenesis . Recent studies have shown that a variety of cancer cells can upregulate the expression of VEGFA, thereby promoting tumor‐induced angiogenesis . With this in mind, we used the CAM assay to test the anti‐angiogenic effect of liposomal formulations.…”
Section: Discussionmentioning
confidence: 99%